Relationship Between Mother's Parenting Patterns and The Incidence of Stunting in Children Aged 2-5 Years - Roza, Siska Desta; Novianti, Novianti; Puspitasari, Ayu Jani; Sari, Putri Permata (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2024)
Stunting is a posture that is not maximal and cognitive abilities are reduced due to chronic malnutrition conditions. The highest prevalence of stunting at 35% was South Asia followed by East and South Africa at 34.1% and West and Central Africa at 33.7% . The upbringing that parents give to the child becomes a very important point to pay attention to. Most likely the occurrence of stunting in the child is significantly influenced by the parenting of the parents. To find out the relationship between maternal parenting and stanting incidence in children aged 2-5 years in Kumbang Village, Blang Mangat District, Lhokseumawe City in 2023 This type of research This type of research is analytical observation research with case control design. Samples in this study are as many as Number of case samples and controls using a 1:1 ratio so that the number of case samples is equal to the number of control samples i.e. 30 case samples, 30 control samples, sampling is done by proportional stratified simple random sampling. There was a significant relationship between health care and stunting incidence in children aged 2-5 years (p = 0.017, OR = 6,000). This means that less health care would be at risk as many as 6,000 times of causing stunting events